INCREASING LESSON EFFICIENCY FOR PRESCHOOL AND PRIMARY EDUCATIONAL CHILDREN USING INTERACHED ENGLISH METHODS AND TECHNOLOGIES - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2022)
This article describes how to increase the effectiveness of English lessons for preschool and primary school children using interactive methods and technologies, as well as to further increase children’s interest.